Controversies in the Pharmacological Treatment of Uveitis - J. Barry, Robert; K. Denniston, Alastair (Current Pharmaceutical Design, 2015)
Uveitis is a term applied to a broad range of conditions characterized by intraocular inflammation. The pharmacological treatment of uveitis is controversial, with limited high-level evidence to inform most of the key treatment decisions that face the patient and clinician on a daily basis. In this review we identified twelve systematic reviews (including two Cochrane reviews) focused on key therapeutic questions in infectious and noninfectious uveitis. Our analysis of these reviews demonstrates the paucity of trial evidence available to inform these important clinical decisions. We consider the reasons for this, and look at the way forward for clinical trials in uveitis, so that we can move from controversy to clarity in the pharmacotherapy of uveitis.
Keywords: randomized clinical trial